Analisis Rantai Pasok Toko Ban dengan Penerapan SCOR dan AHP - An-Nisa Firardiansyah Prayitno; Azhar Eka Putra Lasena; Sandhy Fernandez (Journal of Computer System and Informatics (JoSYC), 2023)
The research carried out aims to describe the supply chain of XYZ Tire Shop using the SCOR (Supply Chain Operations Reference) and AHP (Analytical Hierarchy Process) methods. The SCOR method is used to understand and identify important elements in the supply chain, including suppliers, production, distribution and customers. Furthermore, the AHP method is used to evaluate and prioritize relevant criteria in decision making, such as supplier selection, risk management, and distribution improvement. By integrating SCOR and AHP, XYZ Tire Shop can improve their operational efficiency and supply chain performance. This analysis provides valuable insight into optimizing coordination with suppliers, inventory management, and investments in distribution improvements. The results of this research provide practical guidance for XYZ Tire Shop in improving the best decision making in managing their supply chain. And it can be concluded that the best tire recommendation for procurement of goods is Bristone 205/65 R16 Ecopia.